Structural steelwork : design to limit state theory. - Lam, Dennis; Ang, Thien Cheong; Chiew, Sing-Ping (CRC Press, 2013)
"The fourth edition of a perennial bestseller, this book describes the design theory and code requirements for common structures, connections, elements and frames and contains detailed explanations of the principles underlying steel design for final year undergraduate students reading structural and civil engineering. The chapters have been updated and rearranged to comply with with Eurocode 3. It includes theory for students and practical information for those currently working in the field who require an introduction to the Eurocodes. Every topic is illustrated with fully worked examples, and problems are also provided for practice"--